2009
DOI: 10.1371/journal.pone.0005251
|View full text |Cite|
|
Sign up to set email alerts
|

The Post-Synaptic Density of Human Postmortem Brain Tissues: An Experimental Study Paradigm for Neuropsychiatric Illnesses

Abstract: Recent molecular genetics studies have suggested various trans-synaptic processes for pathophysiologic mechanisms of neuropsychiatric illnesses. Examination of pre- and post-synaptic scaffolds in the brains of patients would greatly aid further investigation, yet such an approach in human postmortem tissue has yet to be tested. We have examined three methods using density gradient based purification of synaptosomes followed by detergent extraction (Method 1) and the pH based differential extraction of synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 47 publications
(77 reference statements)
2
53
0
Order By: Relevance
“…Using synaptosomes as a starting point, highly enriched PSDs were isolated using density gradient purification, detergent extraction, and pHbased differential extraction. The authors concluded that a PSD fraction can be isolated from human postmortem brain tissues with a reasonable degree of integrity (Hahn et al, 2009). Another group has used high-speed centrifugation, detergents, and sucrose gradients to isolate a 'detergentresistant membrane fraction' that they refer to as membrane microdomains (Behan et al, 2009;Parkin et al, 1999).…”
Section: Biochemical Enrichment Of Postsynaptic Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using synaptosomes as a starting point, highly enriched PSDs were isolated using density gradient purification, detergent extraction, and pHbased differential extraction. The authors concluded that a PSD fraction can be isolated from human postmortem brain tissues with a reasonable degree of integrity (Hahn et al, 2009). Another group has used high-speed centrifugation, detergents, and sucrose gradients to isolate a 'detergentresistant membrane fraction' that they refer to as membrane microdomains (Behan et al, 2009;Parkin et al, 1999).…”
Section: Biochemical Enrichment Of Postsynaptic Densitiesmentioning
confidence: 99%
“…The PSD is perhaps the most well-characterized microdomain in the CNS, and several groups have developed cutting edge approaches to interrogate this complex structure in postmortem brain (Cheng et al, 2010;Fernandez et al, 2009;Hahn et al, 2009;MacDonald et al, 2012). Identification and characterization of novel microdomains is currently feasible using standard biochemical techniques.…”
Section: Fluorescence Activated Cell Sorting (Facs) and Single-cell Mmentioning
confidence: 99%
“…Synaptosomes were prepared by the method of Hahn et al with minor modifications (Hahn et al, 2009). Briefly, the cerebral cortical tissue was homogenized using a Dounce type glass homogenizer (Small Clearance, Kontes Glass Co.) with 40 strokes in 1 ml of homogenization buffer (320 mM sucrose, 0.1 mM CaCl 2 , 1 mM MgCl 2 ) supplemented with protease and phosphatase inhibitor cocktails (Sigma-Aldrich, St.Louis, MO, USA).…”
Section: Isolation Of Synaptosomes From Rat Cerebral Cortical Samplesmentioning
confidence: 99%
“…129 Thus, our findings implicating cytoskeletal function and CME may be related. Future work will need to consider the functional aspects of CME within cellular domains such as within the postsynaptic density 130 where CME changes would directly affect NMDA recycling.…”
Section: Commentmentioning
confidence: 99%